Acute bilateral simultaneous angle closure glaucoma after topiramate administration: a case report - Chalam Kakarla V; Tillis Tina; Syed Farhana; Agarwal Swati; Brar Vikram S (Journal of Medical Case Reports, 2008)
Abstract Introduction A case of severe acute bilateral angle closure glaucoma with complete visual loss after oral topiramate therapy. Case presentation A 34 year-old woman developed bilateral severe visual loss 2 days after doubling the dosage of topiramate. Her best-corrected visual acuity (BCVA) was counting fingers in both eyes (OU). Intraocular pressures were 49 mm and 51 mm of Hg in right and left eyes respectively, with conjunctival chemosis, corneal edema, shallow anterior chamber and closed angles on gonioscopy. B-scan ultrasound revealed annular peripheral choroidal effusions in both eyes. Conclusion Intraocular pressures and anterior chamber depth were normalized after discontinuation of topiramate and initiation of antiglaucoma therapy. Two weeks later, visual acuities improved to 20/25 in the right eye and 20/40 in the left eye. B-scan ultrasound showed resolution of choroidal effusion. Topiramate, an oral sulpha-derivative medication is known to cause ciliochoroidal effusions, which lead to forward rotation of the ciliary body and displacement of the lens-iris diaphragm, with resultant acute angle closure glaucoma and myopic shift.